ENERGY SECURITY AND DECARBONIZATION: SEEKING A POLITICAL BALANCE IN THE EUROPEAN GREEN DEAL - Buiak, Maksym (Public Management and Policy, 2025)
This article examines the profound shift in EU energy policy in the wake of Russia’s full-scale invasion of Ukraine. This event compelled the Union to reassess the interplay between its long-term decarbonization goals, outlined in the European Green Deal, and the urgent demands of energy security. It revealed deep-seated vulnerabilities stemming from a historical reliance on Russian energy. This study investigates the EU’s policy response and the resulting tensions. The research finds that the primary response was the REPowerEU plan, which merged security imperatives with the existing climate agenda. This reframed decarbonization as a key instrument for attaining strategic autonomy and achieving energy “de-Russification.” While fostering a long-term synergy, this approach has also produced sharp short-term conflicts. Urgent actions, including heightened LNG imports and a temporary reversion to coal, clash with climate targets and introduce the risk of “carbon lock-in.” Further complications arise from divergent national strategies among member states, the threat of “greenflation,” and mounting cybersecurity risks. It is concluded that the war has fundamentally redefined the EU’s Green Deal, shifting its focus from a purely environmental strategy to a critical tool for geopolitical resilience. Although a strong long-term synergy between decarbonization and security is evident, implementing this dual-purpose policy necessitates complex trade-offs. The strategy’s success hinges on the EU’s capacity to resolve internal policy divisions, manage emerging socio-economic challenges, and preserve a unified commitment to its climate objectives.